How much donor financing for health is channelled to global versus country-specific aid functions?. Issue 10011 (12th December 2015) - Schäferhoff, Marco; Fewer, Sara; Kraus, Jessica; Richter, Emil; Summers, Lawrence H; Sundewall, Jesper; Yamey, Gavin; Jamison, Dean T
Summary: The slow global response to the Ebola crisis in west Africa suggests that important gaps exist in donor financing for key global functions, such as support for health research and development for diseases of poverty and strengthening of outbreak preparedness. In this Health Policy, we use the International Development Statistics databases to quantify donor support for such functions. We classify donor funding for health into aid for global functions (provision of global public goods, management of cross-border externalities, and fostering of leadership and stewardship) versus country-specific aid. We use a new measure of donor funding that combines official development assistance (ODA) for health with additional donor spending on research and development (R&D) for diseases of poverty. Much R&D spending falls outside ODA—ie, the assistance that is conventionally reported through ODA databases of the Organisation for Economic Co-operation and Development. This expanded definition, which we term health ODA plus, provides a more comprehensive picture of donor support for health that could reshape how policy makers will approach their support for global health.